A Prospect-Theoretical Interpretation of Momentum Returns - Lukas Menkhoff; Maik Schmeling (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
The puzzling evidence of seemingly high momentum returns is related to an understanding of risk as a simple covariance. If we consider, however, risk in higher-order statistical moments, momentum returns appear less advantageous. Thus, a prospect-theoretical assessment of US stock momentum returns provides a possible direction for explaining this puzzle.
Keywords: G14; G12; G11; 330; momentum trading; market efficiency; prospect theory